Human resource strategic management at the universities: an indigenous model with an emphasis on the role of organizational structure - Ali Reza Rouhani Ghehsareh; Alireza Manzari Tavakoli; Sanjar Salajegheh; Samaneh Mehdizadeh (Shahid Beheshti University of Medical Sciences, 2022)
Background: This study aimed to study the effect of organizational structure and its dimensions including complexity, centralization and formalization on the strategic human resource management (SHRM). Methods: The study was applied-developmental and descriptive-correlational method. Interviews with experts and library studies were used to determine the dimensions of SHRM .The data were collected randomly using a researcher-made questionnaire whose validity and reliability were confirmed from a sample of 140 official staff of the university, with validity (KMO = 0.729) and reliability (Cronbach's alpha = 0.892) confirmed by the experts was used to conduct the study that had 57 items for SHRM in the Universities and 27 items for organizational structure and randomly distributed among 140 university staff and 95 questionnaires were collected. SPSS24 and AMOS23 software were used for data analysis. Results: Complexity, centralization and formalization dimensions, respectively, affect the organizational structure by 0.69, 0.69 and 0.82. The effect coefficients of human resource environment, human resource insight, goals, strategy and human resource systems were, respectively, 0.18, 0.34, 0.76, 0.56 and 0.79. The effect coefficients of the organizational structure and its dimensions (complexity, centralization and formalization) on SHRM in the Universities were, respectively, 0.506, 0.118, 0.142 and 0.360. Conclusion: A lot of attention has to be paid to the level of human resource activity to maintain the Universities in this critical competitive position and upgrade it from administrative duties to aligning with the level of business strategy and as an important decision maker.